2008
DOI: 10.1073/pnas.0804979105
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of Globo H and SSEA3 in breast cancer stem cells and the involvement of fucosyl transferases 1 and 2 in Globo H synthesis

Abstract: We examined the expression in breast cancer stem cells (BCSCs) of Globo H, a potential tumor-associated antigen for immunotherapy of epithelial cancers including breast cancer. Flow cytometry revealed Globo H expression in 25/41 breast cancer specimens (61.0%). Non-BCSCs from 25/25 and BCSCs from 8/40 (20%) expressed Globo H. We showed the expression of stage-specific embryonic antigen 3 (SSEA3), the pentasaccharide precursor of Globo H, in 31/40 (77.5%) tumors. Non-BCSCs from 29/31 and BCSCs from 25/40 (62.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
159
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 152 publications
(166 citation statements)
references
References 38 publications
2
159
0
Order By: Relevance
“…Moreover, higher levels of anti-GH Ab were detected in the plasma of breast cancer patients (18)(19)(20). Our previous study also revealed that the expression of some glycans, such as GH and Stage-specific embryonic antigen 3 (SSEA3) (also called Gb5), was observed on breast cancer cells and breast cancer stem cells (BCSCs) (21). All these findings support a rationale for development of carbohydrate-based vaccines based on these cancerspecific glycans.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…Moreover, higher levels of anti-GH Ab were detected in the plasma of breast cancer patients (18)(19)(20). Our previous study also revealed that the expression of some glycans, such as GH and Stage-specific embryonic antigen 3 (SSEA3) (also called Gb5), was observed on breast cancer cells and breast cancer stem cells (BCSCs) (21). All these findings support a rationale for development of carbohydrate-based vaccines based on these cancerspecific glycans.…”
mentioning
confidence: 58%
“…Previously, we have shown the expression of GH and SSEA3 in breast cancer cells and the CD44 + /CD24 low/− BCSC population from clinical specimens (21). However, this CD44/CD24 BCSC system is not applicable to all specimens.…”
Section: Expression Profiles Of Gh-related Structures In Breast Cancementioning
confidence: 99%
“…This result, together with the observation of Globo H expression in only six of the GBM cell lines we tested, indicates that SSEA-4 is the major globo-series GSL in GBM and that, once SSEA-3 is synthesized, it is converted efficiently to SSEA-4 (24). It has been suggested that an α2,3-sialyltransferase, encoded by ST3GAL2 gene, is the major SSEA-4 synthase that is closely related to renal carcinogenesis (36) and that the mRNA level of ST3GAL2 is increased in renal and colorectal carcinomas (37).…”
Section: Discussionmentioning
confidence: 80%
“…Although globotriosylceramide (Gb3Cer) and globoside (Gb4Cer) constitute the basis of the P-blood group system (21), galactosyl globoside (Gb5Cer) and sialyl galactosyl globoside (sialyl Gb5Cer, SGG, MSGG), also known as "stage-specific embryonic antigen-3" (SSEA-3) and "stage-specific embryonic antigen-4" (SSEA-4) (22), respectively, are cell-surface markers widely used to define human embryonic stem cells (hESCs). Globo-series GSLs also have been observed in tumors: Globo H is overexpressed in many epithelial cancers [e.g., ovarian, gastric, prostate, lung, breast, and pancreatic cancers (23)]; SSEA-3, SSEA-4, and Globo H are expressed not only on breast cancer cells but also on breast cancer stem cells (24,25). Moreover, high-level expression of SSEA-4 and disialosyl galactosyl globoside (disialosyl Gb5Cer) is observed in renal cell carcinoma (26), but whether globo-series GSLs are expressed in GBM is not known.…”
mentioning
confidence: 99%
“…Because SSEA3 and SSEA4 were specifically found on embryonic stem cells (19) and breast CSCs (32,33), as well as on 15 different types of cancer cells, including GBM (21), but not on normal cells, we hypothesized that SSEA3 and SSEA4 would be highly expressed in our defined CD133 hi GD3 hi GSCs. We analyzed the expression of SSEA3 and SSEA4 in the sorted cell population using CD133 and GD3 as markers, and found that more than 31.3% of CD133 hi GD3 hi cells were SSEA3 + and 59.4% were SSEA4 + , whereas less than 10% of CD133 lo GD3 lo cells were positive for SSEA3 and SSEA4 (Fig.…”
Section: Resultsmentioning
confidence: 99%